2017
DOI: 10.1002/suco.201700950
|View full text |Cite
|
Sign up to set email alerts
|

Predictive strength of ready‐mixed concrete: Exemplified using data from the Norwegian market

Abstract: A hierarchical model for the variability of material properties in ready-mixed concrete is formulated. The model distinguishes between variation on the batch, recipe, plant, producer, durability class, strength class, and regional standard level. By considering Bayesian inference and maximum likelihood estimators, the contributions from the different hierarchical levels to the variability can be estimated. The methodology is demonstrated by considering more than 14,000 compressive strength recordings from Norw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 28 publications
(36 reference statements)
0
17
0
Order By: Relevance
“…The crack widths that are of primary interest from the experimental study and that are comparable to the characteristic crack width, w k , are the 95%‐fractile of the crack widths measured, w 0.95 , for each RC tie. To obtain this value, the statistical method of Engen et al was used to account for the uncertainty related to the limited number of section average crack width measurements for each formed crack. Generally, the mean and the variance of the crack width for a formed crack i with n i section average crack width measurements can be estimated as: yfalse¯i=1nij=1niyi,j, …”
Section: Experimental Studymentioning
confidence: 99%
“…The crack widths that are of primary interest from the experimental study and that are comparable to the characteristic crack width, w k , are the 95%‐fractile of the crack widths measured, w 0.95 , for each RC tie. To obtain this value, the statistical method of Engen et al was used to account for the uncertainty related to the limited number of section average crack width measurements for each formed crack. Generally, the mean and the variance of the crack width for a formed crack i with n i section average crack width measurements can be estimated as: yfalse¯i=1nij=1niyi,j, …”
Section: Experimental Studymentioning
confidence: 99%
“…A typical value applicable to different strength classes was used for the concrete cylinder strength. The V may seem slightly high compared to the results reported by, say, [25], but may be realistic in the case of a deteriorated structure. Furthermore, a sensitivity study by one of the authors [15] showed only a minor influence of Young's modulus on the anchorage capacity.…”
Section: Geometric and Physical Uncertaintymentioning
confidence: 55%
“…Note that in the literature, usually only one experimental outcome is reported for each experimental setup, such that in Table 1, mi=m=1, and the generalized estimator in Equation () takes the form in Equation (). There are, however, examples of experimental campaigns being repeated by independent researchers. θik=RexpRNLFEA,ki When Equation () is used, the contributions to the estimate from within‐ and between‐model uncertainty can be quantified by following a hierarchical approach as suggested by 6 …”
Section: Quantification Of the Modelling Uncertaintymentioning
confidence: 99%
“…It can be shown that y can be represented by a t‐distributed random variable with expected value and variance given in Equations () and (), where νk=nk1 are the degrees of freedom. See for example 6 for derivations. The mean and coefficient of variation of θ can be estimated from Equations () and (), where the errors of approximation in Equations () and () are <2% for Vθk<0.2. 6 μnormalyk=normalE[]yk=ytrue¯k σnormalyk2=VAR[]yk=νk()νk+2()νk2()νk+1sk2 μθk=normalE[]θkexp0.35emytrue¯k VθkVAR[]yk=skνkνk+2νk2νk+10.25em The effect of the degrees of freedom, that is, the number of observations or the decreasing statistical uncertainty, on the ratio between the calculated standard deviation σy and the sample standard deviation ...…”
Section: Quantification Of the Modelling Uncertaintymentioning
confidence: 99%
See 1 more Smart Citation